(The Effect Pulp, Compound of Pulp and Peel and Extraction Methods on the Characteristic of Avocado Oil (Persea Americana Miller) - H G. Pohan; Bakri Rosidi; Ade Herman Suherman (Balai Besar Industri Agro, 2005)
The study on oil extraction of avocado fruit has been conducted on the effect of rwa materials and extraction method on the characteristic of avocado oil.There are two method : soaking treatment and fermentation treatment before pressing to separate the oil from avocado fruits.The solvent were hexane,diethyl ather and alcohol, whereas the fermentation times were 3,5 and 7 days.Based on the study the subtances compositions of avocado fruit were 71.72% pulp 9.51% peel and 18.77% seed.The result indicated that the best treatment for oil extraction were obtained by using the diethyl ether soaking of dried fruit and 3 days fermentation of pulp before pressing.The first treatment have produced the yield 37.76% oil,4.20% free fatty acid 2,07 mg/100 gram vitamin E, 102 IU/100 gram vitamin A and 10.3 mg/gram beta karoten while the second treatment has produced the yield 21,44% oil,7,85% free fatty acid ,1,40 mg/100 gam vitamin e ,0,5 IU/100 gram vitamin a and 18,1 mg/gram b karoten.